Mesoscopic imaging of glioblastomas: Are diffusion, perfusion and spectroscopic measures influenced by the radiogenetic phenotype? - Demerath, Theo; Simon-Gabriel, Carl Philipp; Kellner, Elias; Schwarzwald, Ralf; Lange, Thomas; Heiland, Dieter Henrik; Reinacher, Peter; Staszewski, Ori; Mast, Hansjörg; Kiselev, Valerij G.; Egger, Karl; Urbach, Horst; et al. (Neuroradiology Journal, 2017)
The purpose of this study was to identify markers from perfusion, diffusion, and chemical shift imaging in glioblastomas (GBMs) and to correlate them with genetically determined and previously published patterns of structural magnetic resonance (MR) imaging. Twenty-six patients (mean age 60 years, 13 female) with GBM were investigated. Imaging consisted of native and contrast-enhanced 3D data, perfusion, diffusion, and spectroscopic imaging. In the presence of minor necrosis, cerebral blood volume (CBV) was higher (median ± SD, 2.23% ± 0.93) than in pronounced necrosis (1.02% ± 0.71), pcorr = 0.0003. CBV adjacent to peritumoral fluid-attenuated inversion recovery (FLAIR) hyperintensity was lower in edema (1.72% ± 0.31) than in infiltration (1.91% ± 0.35), pcorr = 0.039. Axial diffusivity adjacent to peritumoral FLAIR hyperintensity was lower in severe mass effect (1.08∗10-3 mm2/s ± 0.08) than in mild mass effect (1.14∗10-3 mm2/s ± 0.06), pcorr = 0.048. Myo-inositol was positively correlated with a marker for mitosis (Ki-67) in contrast-enhancing tumor, r = 0.5, pcorr = 0.0002. Changed CBV and axial diffusivity, even outside FLAIR hyperintensity, in adjacent normal-appearing matter can be discussed as to be related to angiogenesis pathways and to activated proliferation genes. The correlation between myo-inositol and Ki-67 might be attributed to its binding to cell surface receptors regulating tumorous proliferation of astrocytic cells.
CRIS-Team Scopus Importer:2024-03-07
Keywords: diffusion imaging; glioblastoma; perfusion imaging; proton spectroscopy; Radiogenomics